(untitled) (FUDMA JOURNAL OF SCIENCES, 2023)
Nigeria’s economy depends on oil and one of the important activities in oil production is drilling in the presence of drilling fluid. A major component of drilling fluid that determines the success of a drilling operation is bentonitic clay. In this study, a local Bentonitic clay from Dikwa formation was procured and characterized by; x-ray diffraction, x-ray fluorescence, cation-exchange capacity and particle size distribution. The clay was beneficiated (wet and dry) using Na2CO3 (concentration ranges from 2-14%wt) as activating agent, and sample drilling muds (fluids) were formulated. Drilling fluids formulated from the beneficiated clay without additive addition did not possess the minimum rheological properties required for use in oil and gas drilling operations. However, an improvement in rheological and filtration properties was observed when treated with carboxy-methyl-cellulose (CMC) as an additive. The optimum values for plastic viscosity, gel strength and fluid loss (8.1cP, 9.4lb/100ft2 and 14mL, respectively) were obtained at 6%wt Na2CO3 concentration. The fluid loss of muds formulated from the local clay was improved by about 50% when treated with (CMC) and meets the API requirements. Results obtained after detailed experimental investigations showed that modified Dikwa (Kaza) bentonitic clay has great potentials to be used as a constituent of oil and gas drilling fluid.